Systematic Literature Review (SLR): Perkembangan Penelitian E-Goverment di Indonsia dengan VOSviewer - Wijaya, Muhamad Ilham; Sari, Dela Puspita; Jarti, Nanda (CV. Information Technology Training Center - Indonesia (ITTC), 2025)
This study aims to analyze the development of e-government research in Indonesia using a Systematic Literature Review (SLR) approach supported by bibliometric analysis using VOSviewer software. The review was conducted on scientific publications obtained from the Google Scholar database between 2020 and 2025. The results indicate that the topic of e-government is strongly linked to themes such as bureaucratic transformation, good governance, digital public services, and information technology literacy. Through network visualization and keyword density, it was found that e-government research in Indonesia has experienced a significant increase in line with the Electronic-Based Government System (SPBE) policy. Furthermore, the analysis results show positive trends in Indonesia's E-Government Development Index (EGDI) and Human Capital Index (HCI), reflecting advances in digital infrastructure, increased public literacy, and the effectiveness of public services. Overall, this study concludes that the implementation of e-government in Indonesia plays a crucial role in realizing transparent, efficient, and sustainable governance, as well as supporting the achievement of the Sustainable Development Goals (SDGs).